Nutritional and functional properties of eleven hybrid and land-race rice varieties from Assam, India - Sharma, S.K.; Mali, Nilpawan; Sharma, R.K.; Barman, D. (South Eastern European Journal of Public Health, 2025)
Rice is one of the most important food crop in the world which provides a primary source of dietary energy, particularly in Asia. It is a flexible and health-promoting staple due to its nutritional richness in carbohydrates, protein, and other essential phytochemicals. This study investigates the proximate composition, functional properties, and biochemical characteristics of eleven rice cultivars from Dhubri district, Assam. Key findings indicate that varieties such as Rupahi, Bahadur Sub-1, Lalpeda, Geda Gedi, Ranjit Sub-1, and Natun Aijong exhibit superior qualities in various parameters. Proximate analysis reveals that the Lalpan variety exhibits the highest fat content (4%), Kola Mota has the highest crude fiber content (2.80%), Bahadur Sub-1 contains the highest protein content (13.77%), Natun Aijong has the highest carbohydrate content (86.54%), and Chapar Aijong shows the highest food energy value (412.1 kcal). In functional properties, Lalpeda demonstrates the highest water absorption capacity (1.2506 g/L) and water solubility index (0.0933 g/L), while Geda Gedi has the greatest swelling power (0.0114). The highest oil absorption index is found in Bahadur Sub-1 (0.348). Additionally, Lalpeda shows the highest total phenolic content (0.0024 μg/mg), Rupahi has the highest total flavonoid content (13.59 mg/g) and amylase content (18.76%), while Natun Aijong has the highest starch content (77.88%). Among all varieties, Rupahi and Bahadur Sub-1 consistently demonstrate enhanced nutritional and functional attributes, identifying them as promising candidates for both cultivation and commercial applications. This research contributes valuable insights into the nutritional diversity of Assamese rice landraces.